Motivational factors of Muslim rape offenders in Sungai Udang Prison, Melaka, Malaysia - Zaizul Ab Rahman (Penerbit Universiti Kebangsaan Malaysia, 2021)
The issue of rape in Malaysia showed an increase from 138 cases in 1980 to the 4816 figure in 2011 and 13,272 in 2017. This leads to the need for a study to identify the criminal profile in dealing with rape, inducement factors that drive muslim rapists commit rape and knowing the rules of the rehabilation program is clearly used by prisons to rehabilitate criminals rape. Approach to field studies covering aspects of data collection procedures, instruments, research and pilot studies that spefically used in looking at factors drive these criminals commit rape and rape recovery programs in Sungai Udang Prison, Malacca. For this purpose a total of 132 muslim prisoners Sungai Udang Prison are made samples. In addition the method of sample observations and interviews with significant individuals also used in this study. The main findings of the studies obtained was the main factor for the occurence of rape sexual stimulation that is too widespread.